Izbrani primeri upravljanja območij s kulturno dediščino - Nared, Janez; Razpotnik Visković, Nika (CAPAcities, 2014)
Selected Examples of Managing Cultural Heritage AreasCultural heritage can make an important contribution to development, especially if it is conscientiously managed and if one is aware of all of its development potentials. Attention was drawn to this in the CHERPLAN project with the volumes Upravljanje območij s kulturno dediščino (Managing Cultural Heritage Areas) and Managing Cultural Heritage Sites in Southeastern Europe~these two related books are now complemented by a third volume that discusses selected examples of managing cultural heritage areas. Because the project was intended to promote the development of areas in southeast Europe, we first present heritage from this area on the UNESCO World Heritage List, then various systems of protecting cultural heritage, followed by intergovernmental efforts to protect cultural heritage in southeast Europe. Regarding the content, we addressed the multifunctional role of cultural heritage, and due to specific circumstances in the past two decades we have also highlighted the damage caused to cultural heritage by military conflicts. The following individual examples of cultural heritage management are discussed: Kotor, Gamzigrad, the Stari Grad Plain, Ohrid, the Mehmed Paša Sokolović Bridge, Lake Neusiedl, and the Semmering Railway, and outside the southeast Europe program area also Bilbao and the Rhaetian Railway.